Model Komunikasi Guru Dan Siswa Dalam Meningkatkan Prestasi Non-Akademik Melalui Virtual Learning - Baiq Zil Karimah (Program Studi Komunikasi dan Penyiaran Islam Fakultas Dakwah UIN Sultan Maulana Hasanuddin Banten, 2023)
The communication model is a simple description of the communication process that occurs both individually and in groups. The use of this communication model is considered effective in the success of communication because the message delivered can be received by the target. In this case, what happened at Pacet 1 Public High School implementing virtual learning by utilizing the media as an intermediary, this communication model also has obstacles that occur when communicating between teachers and students such as broken sounds, missing pictures, and so on. This study aims to determine the teacher and student communication model in improving non-academic achievement through virtual learning. This study used the Shannon and Weaver communication model theory. The informants here are the headmaster of SMA Negeri 1 Pacet, the supervising teacher for the competition, and several students. Data is collected by observation, interviews, and documentation. Data validity was carried out using triangulation techniques. The results of this study indicate that in the Shannon and Weaver communication model, communication requires Information Resources (SDI) which then forms messages to be communicated through intermediaries such as smartphones using internet channels. but in the process of communication, the virtual is not free from interference (noise). And the authors see that the communication process used by teachers and students at SMA Negeri 1 Pacet is quite effective and efficient so that it can hone children's creativity.